2019
DOI: 10.1073/pnas.1902276116
|View full text |Cite
|
Sign up to set email alerts
|

From thought to action: The brain–machine interface in posterior parietal cortex

Abstract: A dramatic example of translational monkey research is the development of neural prosthetics for assisting paralyzed patients. A neuroprosthesis consists of implanted electrodes that can record the intended movement of a paralyzed part of the body, a computer algorithm that decodes the intended movement, and an assistive device such as a robot limb or computer that is controlled by these intended movement signals. This type of neuroprosthetic system is also referred to as a brain-machine interface (BMI) since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 76 publications
3
49
0
Order By: Relevance
“…It allows the patient to have more control over planned movements. On top of that, the involved PPC sub-regions, like the parietal reach region, have the ability to direct both body sides upon single area stimulation [78,79]. Its capability of partially mixed encoding in which neurons respond to multiple variables only adds to its strength [80,81].…”
Section: Potential Target For Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…It allows the patient to have more control over planned movements. On top of that, the involved PPC sub-regions, like the parietal reach region, have the ability to direct both body sides upon single area stimulation [78,79]. Its capability of partially mixed encoding in which neurons respond to multiple variables only adds to its strength [80,81].…”
Section: Potential Target For Rehabilitationmentioning
confidence: 99%
“…PPC area 5, the parietal reach region, AIP and LIP, located in the intraparietal sulcus [34, 79,83] or area MMA in mice show the most potential as implant targets [39]. However, just as for sensory type implants, a double approach could lead to the best outcome.…”
Section: Potential Target For Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…We recorded from on average 101.6 ± 7.2 neurons ( Figure 1—figure supplement 1 ) over 14 sessions in the PPC (left hemisphere) of a tetraplegic human participant (spinal injury at levels 3–4; C3/4). In previous work, we referred to the implant area as the anterior intraparietal cortex, a region functionally defined in NHPs ( Aflalo et al, 2020 , Aflalo et al, 2015 ; Rutishauser et al, 2018 ; Zhang et al, 2017 ; Zhang et al, 2020 ; Andersen et al, 2019 ; Sakellaridi et al, 2019 ). Here, we refer to the recording site as the PC-IP, acknowledging that further work is necessary to definitively characterize homologies between human and NHP anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…They trace the course of basic research on monkeys that identified the brain circuits underlying limb movement, and identified the brain location where stimulation should reduce tremor, and did. The next two articles by Kennedy and Schwartz (14) and by Andersen, Aflalo, and Kellis (15) provide dramatic examples, showing how understanding the organization of the monkey brain's control of limb movements led to the development of prosthetic devices that enable paralyzed human patients to control artificial arms with activity from their own brains. This is possible because of the similarity of the functional anatomy of the parts of monkey and human brain that control of limb movement; these structures are strikingly different in rodents.…”
Section: Restoring Motor and Sensory Functionmentioning
confidence: 99%